HMGB1 is a key factor for tamoxifen resistance and has the potential to predict the efficacy of CDK4/6 inhibitors in breast cancer. Issue 4 (26th February 2021) - Zhang, Han; Wang, Jinlu; Li, Jingtong; Zhou, Xiaoping; Yin, Lei; Wang, Yiran; Gu, Yucui; Niu, Xingjian; Yang, Yue; Ji, Hongfei; Zhang, Qingyuan
Abstract: Breast cancer is the leading cause of cancer death in women. Hormone‐receptor‐positive breast cancer (HR + BC) is the most common pathological type of breast cancer, of which the main treatment method is endocrine therapy. Unfortunately, primary or acquired drug resistance greatly limits its efficacy. In recent years, the newly launched CDK4/6 inhibitors could effectively reverse endocrine resistance in breast cancer. However, considering their expensive price and side effects, it is particularly important to find out effective biomarkers and screen sensitive patients. Here, we found through bioinformatics analysis that high mobility group box 1 (HMGB1) expression increased in endocrine‐resistant HR + BC. In clinical specimens, the higher expression of HMGB1 was associated with shorter progression‐free survival (PFS) for HR + BC patients with endocrine therapy after surgery. For endocrine‐resistant breast cancer, compared with HMGB1‐negative patients, HMGB1‐positive patients who received CDK4/6 inhibitors treatment benefited more in PFS. Moreover, we demonstrated that HMGB1 promoted tamoxifen resistance by combining with the Toll‐like receptor 4 (TLR4) and activating nuclear factor kappa B (NF‐κB) pathway. CDK4/6 inhibitors could downregulate the expression of HMGB1 and suppress the TLR4‐NF‐κB pathway, and in turn reverse tamoxifen resistance. These results illuminated the critical role of HMGB1 in the process of tamoxifen resistance, explained the mechanism of CDK4/6 inhibitors reversing tamoxifen resistance, and suggested the feasibility of HMGB1 as a potential biomarker for screening sensitive patients receiving CDK4/6 inhibitors. Abstract : This article illustrated the critical role of HMGB1 in the process of endocrine therapy resistance, explained one of the mechanisms of CDK4/6 inhibitors reverse endocrine therapy resistance, and suggested the feasibility of HMGB1 as a potential biomarker for screening sensitive patients receiving CDK4/6 inhibitors.